American cocktail : a "colored girl" in the world - Reynolds, Anita Thompson Dickinson, 1901-1980.; Hutchinson, George, 1953-; Miller, Howard M. (Cambridge, Mass. : Harvard University Press, 2014)
"Rollicking, never-before-published memoir of a fascinating woman with an uncanny knack for being in the right place in the most interesting times. Of racially mixed heritage, Anita Reynolds was proudly African American but often passed for Indian, Mexican, or Creole. Actress, dancer, model, literary critic, psychologist, but above all free-spirited provocateur, she was, as her Parisian friends nicknamed her, an "American cocktail." One of the first black stars of the silent era, she appeared in Hollywood movies with Rudolph Valentino, attended Charlie Chaplin's anarchist meetings, and studied dance with Ruth St. Denis. She moved to
Foreword / by Patricia Williams -- Introduction / by George Hutchinson -- A note on the text / by George Hutchinson -- American cocktail -- Appendix 1: Publications by Anita Reynolds -- Appendix 2: Anita Reynolds's correspondence with family.
Includes bibliographical references and index.
Text in English.
Keywords: Reynolds, Anita Thompson Dickinson, -- 1901-1980.; Reynolds, Anita Thompson Dickinson, -- 1901-1980.; African American women -- Biography; Motion picture actors and actresses -- United States -- Biography; African American women entertainers -- Biography; African American psychologists -- Biography; African American psychologists; African American women; African American women entertainers; Motion picture actors and actresses; United States; Autobiographies; Biographies; Autobiographies; Narrative non-fiction.